ANALYSIS OF LAND SPINACH FARMING INCOME IN PERBAUNGAN DISTRICT, SERDANG BEDAGAI REGENCY - Ni'mal Hamdi; Faisal Azhari Baldan Panjaitan; Aadil Hussain Mir (CV. Radja Publika, 2025)
This study aims to analyze the production costs, revenues, and income of land spinach farming in Perbaungan District, Serdang Bedagai Regency. This study uses a survey method with a quantitative descriptive approach. The data used consist of primary data obtained through direct interviews with farmers using questionnaires, as well as secondary data from related agencies. The sampling technique was carried out systematically on land spinach farmers at the research location. Data analysis was carried out using cost, revenue, and farm income analysis. The results showed that the total production costs of land spinach farming were Rp 7,300,750, with an average of Rp 197,318 per farmer. The total revenue obtained was Rp 27,950,000, with an average of Rp 755,405 per farmer per harvest. The net income obtained by farmers was Rp 20,649,250, with an average of Rp 558,087 per farmer. Based on research results, land kale farming in Perbaungan District is considered profitable and feasible to develop, as the revenue generated exceeds production costs. Therefore, increased efficiency in the use of production factors and government support in maintaining price stability are needed to improve farmer welfare.